Renegotiating the Body : Feminist Art in 1970s London. - Battista, Kathy (I.B. Tauris, 2012)
What makes art 'feminist art'? Although feminist artists do have a unique aesthetic, there can be no essential feminist aesthetic, argues Kathy Battista in this exciting new art history. Domesticity, the body, its traces and sexuality have become prominent themes in contemporary feminist practice but where did these preoccupations begin and how did they come to signify a particular type of art? Kathy Battista's (re- )engagement with the founding generation of female practitioners centres on 1970s London as the cultural hub from which a new art practice arose. Emphasising the importance of artis.